Motor unit activity within the depth of the masseter characterized by an adapted scanning EMG technique - Dijk, Hans van; Eiglsperger, U.; Hellmann, Daniel; Giannakopoulos, Nikolaos Nikitas; McGill, K. C.; Schindler, Hans J.; Lapatki, B. G. (Clinical neurophysiology, 2016)
Objective - To study motor unit activity in the medio-lateral extension of the masseter using an adapted scanning EMG technique that allows studying the territories of multiple motor units (MUs) in one scan. - Methods - We studied the m. masseter of 10 healthy volunteers in whom two scans were performed. A monopolar scanning needle and two pairs of fine-wire electrodes were inserted into the belly of the muscle. The signals of the fine wire electrodes were decomposed into the contribution of single MUs and used as a trigger for the scanning needle. In this manner multiple MU territory scans were obtained simultaneously. - Results - We determined 161 MU territories. The maximum number of territories obtained in one scan was 15. The median territory size was 4.0mm. Larger and smaller MU territories were found throughout the muscle. - Conclusions - The presented technique showed its feasibility in obtaining multiple MU territories in one scan. MUs were active throughout the depth of the muscle. - Significance - The distribution of electrical and anatomical size of MUs substantiates the heterogeneous distribution of MUs throughout the muscle volume. This distributed activity may be of functional significance for the stabilization of the muscle during force generation.
Gesehen am 29.05.2020